Rapid food desensitization associated with omalizumab before oral immunotherapy - Bruna Giavina-Bianchi, MD; Pedro Giavina-Bianchi, MD, PhD (World Allergy Organization Journal)
In this report, we propose an innovative approach to managing patients with food-induced anaphylaxis by performing rapid food desensitization alongside the use of omalizumab as an introductory step to oral immunotherapy. This combined strategy aims to enhance both the safety and effectiveness of the process, which seeks to induce immunological tolerance to food allergens, while reducing the risk of severe allergic reactions during treatment. The use of omalizumab helps prevent anaphylaxis and improves the patient's ability to tolerate the allergen. Rapid desensitization offers significant time and cost savings. As more scientific evidence supports rapid food desensitization, it could become a valuable tool for clinicians managing food-induced anaphylaxis, offering a promising avenue for the treatment of food allergies, especially in complex cases.